The RNA helicase eIF4A as a novel target in insect cells to combat arboviral infections - Tanja Rehling; Kim Mentchen; Leonie Konopka; Wiebke Obermann; Friedemann Weber; Patrick Schmerer; Marc F. Schetelig; Arnold Grünweller; Irina Häcker; Francesca Magari (PLoS ONE, 2026)
Arthropod-borne viruses cause major global health burdens, yet few vaccines or antivirals exist. Targeting host factors required for viral replication offers a promising approach. The DEAD-box RNA helicase eIF4A, a core component of the translation initiation complex eIF4F, unwinds structured 5′ UTRs and is therefore critical also for the translation of many viral RNAs. The compound classes rocaglates and pateamines are potent eIF4A inhibitors in mammalian cells. Here we show that the natural rocaglate silvestrol strongly inhibits Rift Valley fever virus replication (RVFV) in human cells without cytotoxicity, expanding the list of eIF4A-dependent arboviruses. Moreover, we studied eIF4A function and rocaglate/pateamine sensitivity in insects, specifically in the arboviral vector Aedes aegypti and the fruit flies Anastrepha suspensa and Drosophila melanogaster . Sequence analysis showed conservation of the rocaglate-binding motif between the human eIF4A and all three insects. Dual luciferase assays in insect cell lines confirmed selective translation inhibition from purine-rich reporters by silvestrol below cytotoxic thresholds. Purified eIF4A variants from all three insect species retained helicase activity, allowing direct testing of inhibitor interactions. Thermal shift assays demonstrated robust stabilization of eIF4A–RNA complexes by both compound classes in the wildtype proteins, with unexpected rocaglate sensitivity of the putatively insensitive Ae. aegypti H161L mutant, indicating a unique binding pocket geometry of the mosquito protein. In summary, our results present RVFV as another drug target for eIF4A inhibitors and highlight comparative biochemistry studies providing insights into distinctive eIF4A inhibitor binding site architecture, with the prospect of exploring informed design to develop species-specific inhibitors.